Istanbul Office Market: Determining tenants satisfaction with their office and environmental quality - Lale Berkoz; Merve Sakar (European Regional Science Association (ERSA), 2011)
The effects of the social and spatial transformation caused by globalization can also be seen within the Istanbul metropolitan area. The growth of the service sector in Istanbul since the 1980s may be attributed to the expansion of foreign multinational corporations, transnational banks, growth in international relations, extension of foreign trade and enlargement of business size. Within this process, a need for qualified and user friendly office areas came into existence. This study will investigate the satisfaction and expectations of office tenants in Istanbul office market. The data collected in this study were obtained through a survey of 330 office tenants in Istanbul. The survey was conducted by internet interviews during April 2010 (Sakar, 2010). The results of collected data were compared with the study, What Office Tenants Want, that prepared by ULI/BOMA in 1999. The results of this research have particular policy and planning implications for Istanbul and may stimulate the creation of real estate development in developing user-satisfying and well-equipped office buildings for the city center that respond to the desires and needs of FİRE firms with respect to location and mechanical infrastructure necessitated by the new telecommunications systems.
Keywords: 330